2014
DOI: 10.1534/genetics.114.163170
|View full text |Cite
|
Sign up to set email alerts
|

High Intake of Dietary Sugar Enhances Bisphenol A (BPA) Disruption and Reveals Ribosome-Mediated Pathways of Toxicity

Abstract: Bisphenol A (BPA) is an organic compound to which human populations are ubiquitously exposed. Epidemiological data suggest BPA exposure might be associated with higher rates of diabetes and reproductive anomalies. Health concerns also include transgenerational consequences, but these mechanisms are crudely defined. Similarly, little is known about synergistic interactions between BPA and other substances. Here we show that acute and chronic exposure to BPA causes genome-wide modulation of several functionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…To further address the time scale in which coupling between 5S and 45S elements emerges, we investigated the hypothesis that environmental triggers might rapidly induce concerted CN expansions and contractions in the rDNA loci. In particular, it has recently been suggested that bisphenol A (BPA) disrupts the expression of the genes coding for proteins of the small and large ribosome, and could cause nucleolar stress (44). Disruption in the expression of nucleolar components might cause rDNA instability and trigger concerted modulation of rDNA CN across the 5S and 45S loci.…”
Section: Cn Of the 5s Rdna Is Unlinked With Nearby Snp Variation In Tmentioning
confidence: 99%
“…To further address the time scale in which coupling between 5S and 45S elements emerges, we investigated the hypothesis that environmental triggers might rapidly induce concerted CN expansions and contractions in the rDNA loci. In particular, it has recently been suggested that bisphenol A (BPA) disrupts the expression of the genes coding for proteins of the small and large ribosome, and could cause nucleolar stress (44). Disruption in the expression of nucleolar components might cause rDNA instability and trigger concerted modulation of rDNA CN across the 5S and 45S loci.…”
Section: Cn Of the 5s Rdna Is Unlinked With Nearby Snp Variation In Tmentioning
confidence: 99%
“…Here we describe the dataset generated in the study published recently by Branco and Lemos (2014) [11] . The dataset shows that the effect of the organic compound BPA on genome-wide gene expression of D. melanogaster can be enhanced by the ingestion of sugar.…”
Section: Discussionmentioning
confidence: 99%
“…After 5 days laying eggs, adult flies were removed and the vials kept at 25 °C to collect the new emerged flies. Newly emerged adult males were aged for 48 h in the same rearing condition before they were flash-frozen in liquid nitrogen and stored at − 80 °C [11] .…”
Section: Fruit Fly Exposuresmentioning
confidence: 99%
“…The selection of metastable epialleles in Drosophila is well-established in our laboratory ( Ruden et al, 2003 , 2008 , 2009 ; Sollars et al, 2003 ; Ruden and Lu, 2008 ) and in other laboratories ( Carrera et al, 1998 ; Ruden and Lu, 2008 ; Tariq et al, 2009 ; Gangaraju et al, 2010 ; Valtonen et al, 2012 ; Branco and Lemos, 2014 ; Le Thomas et al, 2014 ; Nystrand and Dowling, 2014 ; Somer and Thummel, 2014 ; Stern et al, 2014 ; Wei et al, 2015 ). We showed, for instance, that stress, or the inactivation of the chaperone protein Hsp90, can activate a metastable epiallele of the Kruepple Incomplete facets-1 ( Kr If-1 ) allele, which causes ectopic large bristle outgrowths (ELBOs) to protrude from the eyes ( Sollars et al, 2003 ).…”
Section: The Potential Role Of Natural Selection Of Genetic and Epigementioning
confidence: 91%